Los hábitos de la civilidad; el lugar central de la formación ciudadana en el humanismo cívico (2006)
To overcome the present growing crisis of humanism we need to consider the human person from her specific nature. Thus, we are able to find things which help her to achieve real progress and human flourishing. So, we will start a path that leads us to a civic education, a really humanistic one, such as civic humanism conceives it.